King's Brief Interstitial Lung Disease questionnaire: responsiveness and minimum clinically important difference. Issue 3 (5th September 2019) - Nolan, Claire M.; Birring, Surinder S.; Maddocks, Matthew; Maher, Toby M.; Patel, Suhani; Barker, Ruth E.; Jones, Sarah E.; Walsh, Jessica A.; Wynne, Stephanie C.; George, Peter M.; Man, William D-C.
Health status is increasingly used in clinical practice to quantify symptom burden and as a clinical trial end-point in patients with interstitial lung disease (ILD). The King's Brief Interstitial Lung Disease (KBILD) questionnaire is a brief, validated 15-item, disease-specific, health-related quality of life questionnaire that is increasingly used in clinical trials, but little data exist regarding the minimum clinically important difference (MCID). Using pulmonary rehabilitation as a model, we aimed to determine the responsiveness of KBILD and provide estimates of the MCID. KBILD scores, Chronic Respiratory Questionnaire (CRQ) scores, Medical Research Council (MRC) Dyspnoea score and incremental shuttle walk test (ISWT) distance were measured in 209 patients with ILD (105 with idiopathic pulmonary fibrosis (IPF)) before and after an outpatient pulmonary rehabilitation programme. Changes with intervention and Cohen's effect size were calculated. Anchor-based (linear regression and receiver operating characteristic plots) or distribution-based approaches (0.5sd and standard error of measurement) were used to estimate the MCID of KBILD domain and total scores. KBILD, CRQ, MRC Dyspnoea and ISWT improved with intervention, and the effect sizes of KBILD domain and total scores ranged from 0.28 to 0.38. Using anchor-based estimates, the MCID estimates for KBILD-Psychological, KBILD-Breathlessness and activities, and KBILD-Total were 5.4, 4.4 and 3.9 points, respectively. Using distribution-based methods, the MCID estimate for KBILD-Chest symptoms was 9.8 points. The MCID estimates for KBILD in IPF patients were similar. In patients with ILD and IPF, KBILD is responsive to intervention with an estimated MCID of 3.9 points for the total score. The King's Brief Interstitial Lung Disease (KBILD) questionnaire is responsive to pulmonary rehabilitation in patients with ILD, including those with IPF, with a mean minimum clinically important difference of 3.9 points for KBILD-Total score http://bit.ly/2HXxBIe